2021
DOI: 10.52567/pjsr.v3i4.315
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Medical Waste Management Practices Among Health Care Professionals: A Case Study in District Faisalabad, Punjab Pakistan

Abstract: Biomedical waste (BMW) is produced during surgical, and medical treatment, vaccination, and diagnostic processes. Owing to its hazardous nature BMW must be carefully segregated, handle and discard. As the healthcare professionals are significant and influential part of any healthcare system so their practices for handling this waste are imperative. Purpose: This study was conducted in public sector hospitals of Faisalabad, Punjab, Pakistan to assess the Bio-medical waste management practices among healthcare p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In one of the facilities, Ugbena [37] also discovered the incorporation of members from the local community into such committees, which buttresses the notion that people living around such facilities also need to be aware of the dangers of HCW. Malik et al [9] also observed the poor attention of the HCWM committees in the hospitals studied. A peculiar case observed in China revealed that there is a lack of coordination among the agencies involved in HCWM, which makes it difficult to supervise and monitor the level of compliance with the established policies [40].…”
Section: Availability Of Manuals/guidelines and Waste Management Comm...mentioning
confidence: 93%
See 2 more Smart Citations
“…In one of the facilities, Ugbena [37] also discovered the incorporation of members from the local community into such committees, which buttresses the notion that people living around such facilities also need to be aware of the dangers of HCW. Malik et al [9] also observed the poor attention of the HCWM committees in the hospitals studied. A peculiar case observed in China revealed that there is a lack of coordination among the agencies involved in HCWM, which makes it difficult to supervise and monitor the level of compliance with the established policies [40].…”
Section: Availability Of Manuals/guidelines and Waste Management Comm...mentioning
confidence: 93%
“…A study in Ghana revealed that the majority of healthcare professionals believed that proper HCWM like the use of protective equipment, waste disinfection, and proper disposal had no positive influence in minimizing the risks of infections [20]. Similarly, some studies have shown the indiscriminate and inconsistent use of waste bins by hospital staff, which reflects a poor attitude towards proper HCWM [9,43]. Similarly, Macaulay and Odiase [42] observed a poor attitude among the sanitary staff responsible for collecting and storing HCW, which they attributed to their low level of education and poor training.…”
Section: Attitude To Proper Hcwmmentioning
confidence: 99%
See 1 more Smart Citation